2016
DOI: 10.1155/2016/7972318
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus Delayed Sarcoma Reconstruction: Impact on Outcomes

Abstract: Background. Sarcoma is a rare malignancy, and more recent management algorithms emphasize a multidisciplinary approach and limb salvage, which has resulted in an increase in overall survival and limb preservation. However, limb salvage has resulted in a higher rate of wound complications. Objective. To compare the complications between immediate and delayed (>three weeks) reconstruction in the multidisciplinary limb salvage sarcoma patient population. Methods. A ten-year retrospective review of patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
(12 reference statements)
2
22
0
Order By: Relevance
“…This study highlights that delayed flap reconstruction of the lower extremity is associated with an increased rate of wound complications compared to immediate reconstruction (100% vs. 28.0%, P = 0.001). While our study focuses specifically on the lower extremity, the results remain consistent with the available literature, which comprised of small retrospective cohort studies [2,3,6,7]. Sanniec et al [7] found that delaying reconstruction after sarcoma resection led to an increased number of infections requiring antibiotics (47.1% vs. 9.4%, P = 0.0016).…”
Section: Discussionsupporting
confidence: 84%
“…This study highlights that delayed flap reconstruction of the lower extremity is associated with an increased rate of wound complications compared to immediate reconstruction (100% vs. 28.0%, P = 0.001). While our study focuses specifically on the lower extremity, the results remain consistent with the available literature, which comprised of small retrospective cohort studies [2,3,6,7]. Sanniec et al [7] found that delaying reconstruction after sarcoma resection led to an increased number of infections requiring antibiotics (47.1% vs. 9.4%, P = 0.0016).…”
Section: Discussionsupporting
confidence: 84%
“…Experience regarding the safety of margins in immediate versus delayed free tissue transfer for lower extremity salvage after surgery in cases of soft tissue sarcoma or squamous cell carcinoma, emphasizes the reliability and quality of surgical outcomes, the rate of wound complications, and faster rehabilitation. However, the data do not address outcomes in the context of long-term problems resulting from possible inadequate margins [1,7,28,29]. The timing of reconstructive surgery is frequently highlighted with the bias that immediate or early reconstruction achieves better results with lesser complication rates, however, these studies do not specify how post malignancy excision wounds were cared for in preparation for delayed intervention [4,[28][29][30].…”
Section: Figurementioning
confidence: 99%
“…However, the data do not address outcomes in the context of long-term problems resulting from possible inadequate margins [1,7,28,29]. The timing of reconstructive surgery is frequently highlighted with the bias that immediate or early reconstruction achieves better results with lesser complication rates, however, these studies do not specify how post malignancy excision wounds were cared for in preparation for delayed intervention [4,[28][29][30]. In the presented cohort, in order to avoid infections and subsequent complications in patients scheduled for delayed reconstruction, wounds were temporized with systems completely sealing the resected area (vacuum assisted wound closure devices or skin substitutes).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations